Penerapan Pendekatan Scientific dengan Menggunakan Media Konkret untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas 4 SD - Irwanto Irwanto; Wasitohadi Wasitohadi; Theresia Sri Rahayu (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of this study is to improve student learning outcomes in thematic learning by applying the scientific approach. The number of students studied was 14 students. The results showed that the application of the scientific approach to student learning completeness cycle was only 14% or 4 students who received mastery, increased to 79% or 11 students who completed the first cycle and in the second cycle the learning completeness was reached 100% or all students got mastery value. That is, the learning process using the scientific approach works well. So it can be concluded that the implementation of the steps of learning using the scientific approach can improve the learning outcomes of 4th grade students in Elementary School.